Characteristics of Islamic Character Education and Character Development Methods in the thoughts of Imam Al Ghazali - Junida Fitriani Sitorus; Ira Suryani; Sapri Sapri; Siska Diyah Syahfitri (Universitas Muhammadiyah Enrekang, 2023)
This research explores the characteristics of Islamic character education and methods of character development in the perspective of Imam Al-Ghazali. Imam Al-Ghazali, a prominent scholar and Islamic thinker, contributed significantly to the development of Islamic character within the educational context. The primary focus of this study is to analyze key characteristics of Islamic character education according to Imam Al-Ghazali's perspective and the methods he advocated for building strong character. The research methodology employed content analysis of Imam Al-Ghazali's works, encompassing his views on character education within Islamic teachings. Identified characteristics of character education involve aspects such as morality, integrity, and social responsibility. Furthermore, the study delves into specific methods proposed by Imam Al-Ghazali for nurturing Islamic character. His philosophy emphasizes a holistic approach that encompasses both formal and non-formal educational dimensions, along with spiritual practices in daily life. This research is expected to provide in-depth insights into Imam Al-Ghazali's views on Islamic character education, offer a deeper understanding of the values he aimed to instill, and provide practical guidance for educators interested in implementing these character development methods in the context of modern education.